Dark skin - constitutional or pathological? A X-linked Adrenoleukodystrophy case report - Preto, Clara; Alves, José Eduardo; Fonseca, Marcelo; Santos, Manuela; Miguel, Natalina (BIRTH AND GROWTH MEDICAL JOURNAL, 2018)
Introduction: X-linked adrenoleukodystrophy is a genetically determined peroxisomal disease. Clinical case: An eleven-year-old boy was referred to a pediatric clinic due to generalized hyperpigmentation beginning at the age of six. By ten years of age he started to present behavior changes and decreased school perfomance. History of cutaneous hyperpigmentation was documented in the boy’s maternal uncle. Blood tests were compatible with adrenal insufficiency. Brain Magnetic Resonance Imaging showed frontal leukoencephalopathy. The elevated plasmatic concentration of very long-chain fatty acids and the genotype sequencing of ABCD1 gene established the diagnosis of X-linked adrenoleukodystrophy. The boy´s general condition improved with adrenal insufficiency corticoesteroid treatment however progressive cognitive function deterioration was maintained. Discussion/Conclusion: Early diagnosis and treatment of this rare condition is very important as it can change the disease course. In this case report, given the severity of neurological involvement at diagnosis, no treatment was available to halt neurological disease progression.